Bad data analysis and detection using PMU with UPQC integration to grid during fault conditions - Preeti Nitin Kabra; Suraparaju Venkata Naga Lakshmi Lalitha; Sudha Rani Donepudi (Institute of Advanced Engineering and Science, 2023)
Analysis of bad data in an IEEE 14 bus system with phasor measuring units (PMU) devices is carried out in this paper. The normal operating condition data achieved from the PMU in the bus system is compared to the data achieved during faults in the bus system. A principal component analysis (PCA) technique is proposed in this paper for distinguishing the difference between data transmission during normal and fault conditions. The PCA approach detects the dynamical magnitudes of the measurements taken and also determines the noise caused by the disturbances. The grid system is updated with unified power quality conditioner (UPQC) improvising the parameters of the system to mitigate the fault. The PMU devices use PCA technique for a comparative analysis of the measured components analyzing the performance of the system under different operating conditions. The simulation of these modules is carried out in Simulink environment of MATLAB software with PCA done concerning time.